2001
DOI: 10.1097/00000421-200112000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 676 Cases of Ductal Carcinoma in Situ of the Breast From 1971 to 1995

Abstract: Six hundred seventy-six patients with ductal carcinoma in situ of the breast (DCIS) from 1971 to 1995 were included in the study. Computerized patient files were retrospectively analyzed. Clinical findings were less frequently reported to reveal DCIS after 1989. Positive mammographic findings were obtained in 87% of patients and were mainly represented by microcalcifications (79.4%). Treatment procedures were breast-conserving surgery (BCS) alone (37.5%), BCS followed by radiation (BCSR) (25.5%), or mastectomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
11

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 21 publications
1
19
0
11
Order By: Relevance
“…In the NSABP B-24 study, women < 50 years also display an increase in risk by a factor of 2 [12]. This is confirmed by a range of retrospective series [8,39,42,45,47] (see below). In an overview, Vicini & Recht [48] found that younger women also more often have other unfavorable prognostic factors such as necroses, that they display unfavorable degrees of differentiation and have more advanced tumors.…”
Section: Agementioning
confidence: 69%
See 3 more Smart Citations
“…In the NSABP B-24 study, women < 50 years also display an increase in risk by a factor of 2 [12]. This is confirmed by a range of retrospective series [8,39,42,45,47] (see below). In an overview, Vicini & Recht [48] found that younger women also more often have other unfavorable prognostic factors such as necroses, that they display unfavorable degrees of differentiation and have more advanced tumors.…”
Section: Agementioning
confidence: 69%
“…In a multicentric study, Solin et al [42] observed a lower local recurrence rate after additional irradiation at 9% for free resection margins as compared to 24% for afflicted resection margins (p = 0.03), which was confirmed by two French studies [8,45]. By contrast, Rodrigues et al [30], in a monocentric study, and Solin et al [43], in a first evaluation of the multicentric analysis, found no indication of this.…”
Section: Resection Marginmentioning
confidence: 93%
See 2 more Smart Citations
“…The strongest correlate with recurrence rate is the tissue margin surrounding the DCIS lesion [59]. Most recurrences occur around the original tumor site and are attributed to nonexcised tumor tissue [61]. Therefore, the goal of breast-conserving therapy is to completely excise the lesion obtaining tumor-free margins.…”
Section: Patient Managementmentioning
confidence: 99%